Age and Birth Cohort Differences in Changes in Health Examination Results for Circulatory Diseases cohort phenomena of health check items among worker - Kitamura, Kuniaki (Journal of the Japanese Association for Cerebro-cardiovascular Disease Control, 1993)
In order to understand trends in circulatory diseases. Changes in health status levels of a factory worker population were studied. Health status levels used were “normal”, “moderately abnormal” and “treatment required”. The cohort was comprised of 3, 644 printing or paper manufacturingworkers who had complete records of annual health examinations from 1980 to 1990. The group was divided into 7 birth cohorts with the birth-year range being 5 years, and the change of health statuslevel was observed. Studied were blood pressure, urine test, lipid metabolism, liver function, diabetes mellitus, heart disease and overall evaluation for disease. Blood pressure abnormality increased with age and this relation closely followed Gompertz' law. Birth year appeared not to contribute to blood pressure. Nevertheless, the later the birth year, the number of “treatment required” subjects was less for workers with birh years between 1930 and 1940. The later the birth year, the greater number of “moderate blood pressure abnormality” subjects were observed among those who were born in 1941 or later and who were 45 years of age or younger. For blood lipids and liver function, later birth cohorts experienced an increase in numbers of “moderately abnormal” subjects in younger ages than earlier birth cohorts. Among specific items, triglyceride and gamma -GTP abnormality were the dominant abnormalities. Also, later birth cohorts experienced on increase in numbers of “treatment required” subjects of younger ages with the proportion of the “treatment required” group reaching 10 % in the younger ages, and stablising there after. Among workers with birth years between 1930 and 1935. the later birth cohorts have a higher proportion in the “treatment for heart disease required” group, while later birth cohorts have a lower proportion among the workers who were born in 1936 or later.